2003
DOI: 10.4319/lo.2003.48.1_part_2.0329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of optically shallow bottoms on upwelling radiances: Inhomogeneous and sloping bottoms

Abstract: If the benthic boundary in optically shallow waters is spatially inhomogeneous or sloping, the underwater light field is inherently three-dimensional (3D). Numerical simulations of 3D underwater radiances were made for environmental conditions observed in shallow Bahamian waters. The simulations show that if the pattern of bottom reflectance for an inhomogeneous but level bottom has a spatial scale much smaller than the bottom area seen by a radiometer, the inhomogeneous bottom can be replaced by a homogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 8 publications
0
32
0
1
Order By: Relevance
“…However, within a 1 km 3 1 km pixel, a degree of depth variability and seafloor slope is almost certain. Mobley and Sundman [2003] showed that a sloping seafloor can have an effect on water-leaving radiances and it may be possible to correct for a sloping seafloor to a certain extent by adjusting the solar incidence geometry. Investigating both the effect of a sloping seafloor on SWIM-derived products and a subsequent correction scheme is an interesting avenue of future work.…”
Section: Discussionmentioning
confidence: 99%
“…However, within a 1 km 3 1 km pixel, a degree of depth variability and seafloor slope is almost certain. Mobley and Sundman [2003] showed that a sloping seafloor can have an effect on water-leaving radiances and it may be possible to correct for a sloping seafloor to a certain extent by adjusting the solar incidence geometry. Investigating both the effect of a sloping seafloor on SWIM-derived products and a subsequent correction scheme is an interesting avenue of future work.…”
Section: Discussionmentioning
confidence: 99%
“…Linear spectral mixing at the bottom of the water column was therefore assumed [24]. The figure of 200 spectra per class was determined experimentally to ensure the variation in the in situ libraries was fully exploited while, for computational efficiency, excessive numbers of spectra were not propagated through the model (see Results and Discussion.…”
Section: Component and Classes Descriptionmentioning
confidence: 99%
“…The benthic classes were each initially represented by a set of in situ recorded spectral reflectances linearly mixed according to the benthic composition (Table 3, Figure 4, collection methods given in [24]). In the analysis these basic reflectance spectra were translated by modelling to give total spectral reflectance above the water surface, R t , based on the parameters defined by a given set of the other system component classes and incorporating sensor noise.…”
Section: Radiative Transfer Modelmentioning
confidence: 99%
“…2a). Mobley and Sundman (2003) reasoned 334 that the primary effect of a sloping bottom was to change the 335 solar incidence angle and that the slope could be accounted 336 for by using Lambert's cosine law to correct the radiance 337 computed for a level bottom (i.e., with Hydrolight). We used 338 Eqs.…”
Section: Article In Pressmentioning
confidence: 99%
“…We used 338 Eqs. (9) and (10) of Mobley and Sundman (2003) to 339 compute the radiance from a sloping streambed as…”
Section: Article In Pressmentioning
confidence: 99%